Reliability and validity of Japanese versions of the UCLA loneliness scale version 3 for use among mothers with infants and toddlers: a cross-sectional study - Azusa Arimoto; Etsuko Tadaka (BMC, 2019)
Abstract Background Mothers with infants and toddlers are a potential target population for the prevention or alleviation of feelings of loneliness. However, the theory and methods for measuring loneliness among mothers with infants and toddlers have yet to be standardized worldwide, including in Japan. Our goal was to evaluate the reliability and validity of the Japanese version of the UCLA Loneliness Scale Version 3 (UCLA-LS3-J), as well as two short-form versions-the 10-item UCLA-LS3 (SF-10) and the 3-item UCLA-LS3 (SF-3)-for the measurement of loneliness in mothers with infants and toddlers in Japan. Methods This cross-sectional study was conducted using a self-report questionnaire. The target population was 430 mothers with infants and toddlers who visited a community health center in Yokohama City in Japan. Questionnaire items encompassed the UCLA-LS3-J, as well as demographic data, the feeling for childrearing scale, and measures of social networks and subjective health status. The reliability and validity of the UCLA-LS3-J and its two short-form versions (SF-3 and SF-10) were determined via IBM SPSS Amos and SPSS Statistics 22. Results Questionnaires were returned by 248 mothers (valid response rate: 57.7%) aged 32.7 ± 4.6 (mean ± SD) years. The mean score on the UCLA-LS3-J was 38.4 ± 9.7 (range 20.0-73.0), with a normal distribution. When confirmatory factor analysis was carried out (for a single factor model), the goodness of fit of the model was almost identical to that of the original UCLA-LS3 version for the UCLA-LS3-J: (GFI = 0.882, AGFI = 0.840, CFI = 0.932, RMSEA = 0.066) and SF-10: (GFI = 0.942, AGFI = 0.900, CFI = 0.956, RMSEA = 0.081). The SF-3 model also showed an acceptable fit. The UCLA-LS3-J total score was significantly correlated with the total score on the SF-10 (r = 0.965) and SF-3 (r = 0.868). The Cronbach's α coefficient of the UCLA-LS3-J was 0.926, while those of the SF-10 and SF-3 were 0.888 and 0.790, respectively. The score on the UCLA-LS3-J was positively correlated with childcare burden (r = .319, p < 0.001) and negatively correlated with social networks (r = −.438, p < 0.001). Conclusions This study indicated that the reliability and validity of the UCLA-LS3-J as well as its two short-form versions were adequate for assessing loneliness in mothers with infants and toddlers in Japan.